2003
DOI: 10.3346/jkms.2003.18.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Heparin-Platelet Factor 4 Antibody is a Risk Factor for Vascular Access Obstruction in Patients Undergoing Hemodialysis

Abstract: Since heparin is an anticoagulant commonly used in hemodialysis and the patients on hemodialysis are repeatedly exposed to heparin, heparin may be the cause of the development of heparin-dependent antibodies and thrombotic complications in patients on hemodialysis. The purpose of this study was to determine the prevalence and the clinical significance of the antibodies against heparin-platelet factor 4 complexes as determined by enzyme immunoassay in patients on maintenance hemodialysis. The prevalence of anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Our study confirms that high prevalence of IgG-PF4/H antibodies existed in Chinese patients with haemodialysis, while previous studies found the prevalence ranged from 0 to 12% (3, [8][9][10][11]. The largest and the most comprehensive examination found the prevalence was 1% (5/464) in Caucasians and 17% (4/24) in African-American people, which indicates a difference in races (10).…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Our study confirms that high prevalence of IgG-PF4/H antibodies existed in Chinese patients with haemodialysis, while previous studies found the prevalence ranged from 0 to 12% (3, [8][9][10][11]. The largest and the most comprehensive examination found the prevalence was 1% (5/464) in Caucasians and 17% (4/24) in African-American people, which indicates a difference in races (10).…”
supporting
confidence: 87%
“…Previous studies have shown that serum albumin level was not only a predictor of nutritional status (13), but also a strong predictor of cardiovascular death in maintenance haemodialysis patients (14). This parallel trend further indicates that the presence of IgG-PF4/H antibodies was associated with a significant increase in mortality for patients on maintenance haemodialysis (11).…”
mentioning
confidence: 73%
“…In three of these seven articles, the described assay ultimately served as basis of a commercial assay [12,13,19]. The literature set comprised the remaining 11 articles [10,16,17,[20][21][22][23][24][25][26][27], each of which reported the prevalence of PF4/heparin antibodies in healthy subjects, as assessed by a commercial immunoassay according to manufacturer's directions (Table 1). …”
Section: Literature Data Setmentioning
confidence: 99%
“…In the literature set (Table 1), the PF4/heparin ELISA was used in nine studies [10,16,17,[20][21][22][23][24]26], the PF4/PVS ELISA in three studies [17,24,25], and the PF4/heparin PGIA in three studies [17,24,27]. No study used the PIFA.…”
Section: Literature Data Setmentioning
confidence: 99%
“…There was no significant association between HIA and thrombocytopenia, AVTE or access thrombosis. It has been suggested that asymptomatic but detectable HIA contributes to hypercoagulability and access thrombosis in HD [ 27 , 30 , 43 ]. However, neither our study nor others [ 26 , 32 ] strongly corroborate this finding.…”
Section: Discussionmentioning
confidence: 99%